2019
DOI: 10.3390/nu11112838
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Fasting Glucose, Hemoglobin A1c, and Triglyceride–Glucose Index on Cardiovascular Events in Type 2 Diabetes Mellitus

Abstract: The triglyceride–glucose (TyG) index has been correlated with insulin resistance. We aim to investigate the role of the TyG index on cardiovascular (CV) events in type 2 diabetes mellitus and compare the roles of fasting glucose, hemoglobin A1c, and the TyG index in predicting CV events. This retrospective study enrolled 3524 patients with type 2 diabetes from the Kaohsiung Medical University Research Database in 2009 in this longitudinal study and followed them until 2015. The TyG index was calculated as log … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 41 publications
1
75
3
2
Order By: Relevance
“…Previous clinical data have shown associations of the TyG index to the atherosclerotic cardiovascular diseases, including carotid atherosclerosis [11], coronary artery calcification [12], arterial stiffness [13,14], and CVD [15][16][17][18]. Additionally, our previous study showed that a higher TyG index was associated with an increased risk of cardiovascular events among patients with type 2 DM [19]. Furthermore, Zhao et al [20] reported associations between micro-and macro-vascular damage and the TyG index in an elderly community-dwelling Chinese population.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous clinical data have shown associations of the TyG index to the atherosclerotic cardiovascular diseases, including carotid atherosclerosis [11], coronary artery calcification [12], arterial stiffness [13,14], and CVD [15][16][17][18]. Additionally, our previous study showed that a higher TyG index was associated with an increased risk of cardiovascular events among patients with type 2 DM [19]. Furthermore, Zhao et al [20] reported associations between micro-and macro-vascular damage and the TyG index in an elderly community-dwelling Chinese population.…”
Section: Introductionmentioning
confidence: 73%
“…We found significant trends of stepwise increases in CVA corresponding to the quartile of the TyG index. Our previous study investigated the role of the TyG index in predicting cardiovascular events [19]. Several studies have reported a significant relationship between the TyG index and carotid artery atherosclerosis [11,50].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the TyG index has been found to be well correlated with coronary artery calcification 14 , arterial stiffness 15 , carotid atherosclerosis 16 , coronary artery stenosis 17 , and symptomatic coronary artery disease 18 . Su et al indicated that TyG index appeared to be a stronger predictive factor than glycated hemoglobin (HbA1c) and TGs for cardiovascular events in patients with diabetes 19 . Luo et al firstly reported an association between high TyG index levels and increased risk of major adverse cardiovascular and cerebrovascular events (MACCEs) of patients undergoing percutaneous coronary intervention (PCI) to treat ST-elevation myocardial infarction (STEMI) 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that IR evaluated by TyG index is strongly related to the incidence of diabetes and prediabetic status, suggesting that TyG index may be a considerable predictor for early identifying individuals at high risk of developing diabetes and prediabetes, even performs better than other risk factors such as FBG and weight gain [14-16, 37, 38]. Studies also showed that elevated level of TyG index is prominently associated with an increased risk of developing cardiovascular disease including CAD and ischemic stroke, which suggests evaluation of TyG index might be helpful for identifying people who is susceptible to cardiovascular disease, despite existence of traditional cardiovascular risk factors or not [17,18,[39][40][41]. And for patients with stable CAD, TyG index has been demonstrated to be positively related to future adverse clinical outcomes, indicating that TyG index may play an important role in the prediction of clinical prognosis in patients with stable CAD [42,43].…”
Section: Discussionmentioning
confidence: 99%